Proteolytic Activity of Vibrio parahaemolyticus Isolated from Epinephilus spp. A Preliminary Report - Mienda, Bashir Sajo (Research in Biotechnology, 2012)
Vibrio infection is becoming more and more common worldwide. A Protease producing bacterium was isolated and identified from the eye of Epinephillus spp using phenotypic, morphological and 16S rRNA identification methods. Protease screening was carried out by the caseinolytic method. The unknown bacterium was found to have 98% maximum identity with VibrioÃ‚Â parahaemolyticus in NCBI database after BLAST. The bacterium producesÃ‚Â protease enzyme on a nutrient agar medium containing 10% casein. The aim of this research was to identify the bacterium in question and its ability to produce extracellular proteases, which may be its virulence factor so that its biotechnological application can be explored in future.